Genomic architecture of ecologically divergent body shape in a pair of sympatric crater lake cichlid fishes. Issue 7 (16th December 2013) - Franchini, Paolo; Fruciano, Carmelo; Spreitzer, Maria L.; Jones, Julia C.; Elmer, Kathryn R.; Henning, Frederico; Meyer, Axel
Abstract Determining the genetic bases of adaptations and their roles in speciation is a prominent issue in evolutionary biology. Cichlid fish species flocks are a prime example of recent rapid radiations, often associated with adaptive phenotypic divergence from a common ancestor within a short period of time. In several radiations of freshwater fishes, divergence in ecomorphological traits — including body shape, colour, lips and jaws — is thought to underlie their ecological differentiation, specialization and, ultimately, speciation. The Midas cichlid species complex (Amphilophus spp.) of Nicaragua provides one of the few known examples of sympatric speciation where species have rapidly evolved different but parallel morphologies in young crater lakes. This study identified significant QTL for body shape using SNPs generated via ddRAD sequencing and geometric morphometric analyses of a cross between two ecologically and morphologically divergent, sympatric cichlid species endemic to crater Lake Apoyo: an elongated limnetic species (Amphilophus zaliosus) and a high‐bodied benthic species (Amphilophus astorquii). A total of 453 genome‐wide informative SNPs were identified in 240 F2 hybrids. These markers were used to construct a genetic map in which 25 linkage groups were resolved. Seventy‐two segregating SNPs were linked to 11 QTL. By annotating the two most highly supported QTL‐linked genomic regions, genes that might contribute to divergence in body shape along the benthic–limnetic axis in Midas cichlid sympatric adaptive radiations were identified. These results suggest that few genomic regions of large effect contribute to early stage divergence in Midas cichlids.